PENGARUH MOTIVASI, PENGAWASAN, BUDAYA KERJA DAN FASILITAS KERJA TERHADAP PRODUKTIVITAS KERJA KARYAWAN (Studi Kasus Pada Karyawan PT. PLN (Persero) UIW NTB UP3 Kota Mataram) - M. Akmal Setiahadi; Budi Wahono; Fahrurrozi Rahman (UNIVERSITAS ISLAM MALANG, 2020)
ABSTRAK This research was conducted to analyze the influence of motivation, supervision, work culture and work facilities on the work productivity of employees of PT. PLN (Persero) UIW. NTB UP3 Mataram. The sample in this study were 50 employees who were used as respondents, the method used in this study was multiple linear regression with primary data to be analyzed using the SPSS For Windows application. Based on the research results, simultaneous testing shows that the independent variable has an effect on the dependent variable. The results show that the variables of motivation, supervision, work culture have no effect on employee productivity. The partial test results show that the Work Facility Variable has an effect on the Employee Productivity. Keywords: motivation, supervision, work culture and work facilities on the work productivity of employees